Maternity Leave and the Responsiveness of Female Labor Supply to a Household Shock - Emma Tominey (Institute for the Study of Labor (IZA), 2013)
Female labor supply can insure households against shocks to paternal employment. The paper estimates whether the female labor supply response to a paternal employment shock differs by eligibility to maternity employment protection. We exploit time-state variation in the implementation of unpaid maternity leave through the Family and Medical Leave Act (FMLA) in the US which increased employment protection from 0 to 12 weeks. We find that mothers eligible for FMLA speed up their return to work in response to a paternal shock, with a conditional probability of being in work 53% higher than in households with no paternal shock. In contrast, there was a negligible insurance response for mothers with no employment protection.
Keywords: I30; J13; J20; J64; 330; female labor supply; insurance; maternity leave